Health and safety management assessment among administrative staff and health and safety committee members in University of Sulaimani - Salah Ramzi, Zhian; Faraidoon Abdulwahid, Rahel (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
Abstract: In any occupational field, all staff members, workers, administrators, and managers should know the available occupational health and safety (OHS). In general, the issue of workplace safety could not be achieved effortlessly. Based on the health and safety management system (HSMS) guidelines, a systematic approach should be existing, which employers administer to minimize the available risks of illness and injury. This comprehensive approach consists of identifying, assessing, and controlling the possible risks to the workers. The main challenges of HSMS guidelines are to decrease the possible ambiguity and hazards and proper management of the job. The present study was carried out to evaluate the safety and health management in the University of Sulaimani, its staff's knowledge and attitudes regarding main elements of health and safety management, and the level of the health and safety principles among the university staff. A total number of 135 administrative staff and health and safety committee members were studied in a descriptive cross-sectional study. Two standard questionnaires were used to collect critical data on the participants' health and safety management evaluation and their knowledge, attitude, and skills about health and safety management training programs. The collected data were analyzed through Statistical Package for the Social Sciences version 22. The results indicated that most of the participants (56.3%) worked in colleges and 43.7% in the directorate sector. Their age range was from 25 to 74 years, with more participants belonging to 35-44 and 45-54 years. Most of the participants (68.9%) were males. Regarding the participants' knowledge of and attitude toward managerial aspects of health and safety, it was seen that most of them were well aware. Regarding their health and safety responsibilities, it was concluded that most of them had enough knowledge. In terms of the participant's knowledge of health and safety program components, they had sufficient knowledge of most of the components. The main objective of occupational health and safety assessments is to specify the possible risk to workers and staff members' safety and health. However, the effect of occupational health guidelines within the universities on the improvement of university staff's health and safety has not been clarified precisely yet.